Tax management in the information technology sector: Case study of PT AAS - Herdianti, Alisha Savina; Adriani, Marisa; Cahyatyasma, Damaris; Alifianti, Maisah Zulfa; Kamilia, Andini Dwi; Wijaya, Suparna (Educoretax, 2025)
This study explores the tax management scheme implemented by PT AAS, a company operating in the IT sector, to optimize its tax liabilities while adhering to Indonesian tax regulations. The research investigates the company's tax planning strategies, internal policies, and the effectiveness of its tax management practices. The company has participated in tax amnesty programs but has not yet utilized tax incentives for research and development investments. The study highlights the company's effective internal tax reporting and payment procedures, which are managed without external tax consultants due to the company’s size. Challenges such as late tax reporting due to delayed payments from clients are addressed through internal financial management strategies. Overall, the research underscores the importance of meticulous tax planning and management in ensuring regulatory compliance and optimizing tax liabilities. This case study provides insights into how PT AAS navigates the complexities of tax regulations and maintains a commitment to effective tax management practices